OPTIMIZING STROKE PREVENTION EDUCATION AS AN EFFORT TO CONTROL STROKE INCIDENTS - Arum Dwi Ningsih; Diva Muvidatul Aini; Rusintha Rahma Triandayani (Kirana Publisher, 2026)
Stroke is a health problem that can lead to death and long-term disability. Globally, stroke remains the leading cause of death and neurological deficits. The goal of community service activities is to increase public knowledge about the concept of stroke and its prevention efforts. The methods in this activity are activity coordination, team preparation and educational media, implementation of educational activities and evaluation and program sustainability. The results of community service activities with direct discussions and questions and conducting knowledge level evaluations using the Wilcoxon rank test statistical test are known to have a p value = 0.000 (p <0.005). Therefore, it can be concluded that education on the concept of stroke and its prevention has an impact on increasing public knowledge so that it can change thinking and behavior to be more positive in maintaining body health conditions.